faktor-faktor yang Mempengaruhi Efektivitas Kebijakan Impor Sapi Potong di Propinsi Jawa Barat - D. Yuzaria; D. Suryadi (Universitas Andalas, 2011)
West Java is an imported-beef feedlotter region. Almost 50% of imported cow from Australia are cattled in several district and city. The ammount of cattled imported beef increases every year. Its shows that the implementation of import policy has not been optimal. It did not develop the business of local cattle production. The condition was suspected because of lack of effective implementation of policies by the authorities. This study aims to analyze how the varied pattern of the implementtation of beef import policy reviewed from the aspect of communication, resources, disposition and bureaucratic structure. Research conducted in fifteen distric and city in West Java. This research used the survey method, multistage random sampling, analyzed by using the model of Edward to measure the level policy implementation. The result are, (l) there were pattern variations in import policy implementation: 2) In general, implementation of the import policy, varies from moderate to good. 3) Implementation from the province into districts varies with the medium pattern. 4) Sukabumi, Ciamis and Bandung district is better than the other several district and cities in West Java. Conclussion: policy implementation not yet effective and differs depending on resources.